DEVELOPING STUDENTS’ COGNITIVE COMPETENCIES BASED ON THE ORGANIZATION OF INDEPENDENT WORK (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the pedagogical mechanisms for developing students’ cognitive competencies through the effective organization of independent work in higher education. The relevance of the topic is determined by the growing need to train specialists who are capable of analytical thinking, self-directed learning, problem solving, information processing, and continuous professional development. Independent work is interpreted not only as an additional form of learning activity, but also as an essential didactic condition for strengthening students’ intellectual independence, reflective abilities, research culture, and motivation for knowledge acquisition. The article emphasizes that cognitive competencies are formed more effectively when independent tasks are systematically planned, methodologically supported, differentiated according to students’ abilities, and connected with professional and practical contexts. Special attention is paid to the role of pedagogical guidance, digital educational resources, problem-based assignments, project work, formative assessment, and feedback in improving the quality of students’ independent learning. The study argues that the organization of independent work should be based on clear objectives, gradual complication of tasks, individual learning trajectories, and the integration of theoretical knowledge with practical application. The development of cognitive competencies through independent work contributes to the formation of active, responsible, creative, and professionally prepared graduates who are able to adapt to changing educational and social demands.